Manajerial Kepala Sekolah Dalam Meningkatkan Kinerja Guru - Muhammad Abdillah (Pedir Research Institute, 2023)
This thesis discusses the Managerial Application of Principals in Improving Teacher Performance at Junior High School of Hasan Munadi Beji, Pasuruan Regency. This study aims to: 1) Competence of principals in planning to improve teacher performance at Junior High School of Hasan Munadi Beji, Pasuruan Regency. 2) The competence of the principal in organizing teacher performance improvement at Junior High School of Hasan Munadi Beji, Pasuruan Regency. 3) Competence of school principals in implementing teacher performance improvement in Pasuruan Regency Junior High Schools. 4) Supporting and inhibiting factors of principal managerial competence in improving teacher performance at Junior High School of Hasan Munadi Beji, Pasuruan Regency. This study uses 2 data sources, namely data taken from direct subjects (primary) and data taken from documents (secondary). For data collection in this study using 3 techniques, including: observation, interviews and documentation. The analysis technique is described by reducing the data, then the data is displayed and the last step is drawn into data conclusions or verification (conclusion drawing/verification). The results of this study indicate that the process of implementing principal managerial in improving teacher performance at Hasan Munadi Beji Middle School, Pasuruan Regency includes planning, organizing, implementing efforts to improve teacher performance is quite good. In knowing the supporting and inhibiting factors, several factors that can support the principal's managerial and several factors that can hinder the principal's managerial management have been clearly exposed.